The Political Behavior of Indian American Women: Gendered and Generational Perspectives on Race, Immigration and Socio-Economic Status - Prasad, Shaknar K.; Norlund, Caroline M. (Columbia Journal of Gender and Law, 2010)
On its face, the Indian American’ community’s journey from being ostracized as an “undesirable alien, as a lesser breed, or a benighted heathen” to being heralded as ambassadors of democracy and role models for minority achievement seemingly justifies their celebration as torch bearers of the American dream. Since first arriving on the shores of United States, Indian Americans have tirelessly battled to overcome immigration, naturalization, employment and miscegenation. Correspondingly, they have become the “fastest growing” and “wealthiest minority” in America. Yet, the story does not end there. Behind the scenes of narratives about model minorities breaking down cultural and institutional barriers is another story-the story of multiple generations of Indian women who have arrived in cities such as Los Angeles, Chicago and New York to support their professional husbands. Many of these women are less educated than their husbands and are thrust into a culture that is unfamiliar to them. Once here, they have to navigate their children through the unfamiliar American educational system, set up a household and become integrated into their neighborhoods, participate in potlucks and block parties. Added to these responsibilities is the expectation that they will fulfill their roles as new citizens and participate in the political arena, in most cases, as first-time voters. How these women learn to navigate this new political landscape without the counsel of their mothers, daughters or peers is the driving question of this Article.